MATERNAL RISK FACTORS FOR BIRTH ASPHYXIA IN LOW-RESOURCE COMMUNITIES: SYSTEMATIC REVIEW - Syahputra Damanik, Roni Andre (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Every year, approximately 4 million babies die before reaching their first birthday. The majority of these deaths occur in developing countries, particularly in Asia-Pacific and Sub-Saharan Africa. Perinatal asphyxia is one of the leading causes of perinatal and early neonatal mortality in developing countries, accounting for a quarter of all neonatal deaths and nearly half of all third-trimester stillbirths. Every year, roughly four million babies are born asphyxiated, resulting in one million deaths and one million serious neurological consequences such as cerebral palsy, mental retardation, and epilepsy. Recognizing and managing these risk factors in a timely manner is expected to play a significant role in reducing the often-devastating effects of BA. Given that obstetric care can be inadequate or difficult to obtain in low-resource settings, there is a case to be made for focusing on maternal characteristics that may influence a child's risk of BA. This is due to the fact that these factors may aid in the development of new primary prevention strategies to reduce neonatal mortality and long-term disability. This study presents the incidence of Birth Asphyxia (BA) babies born in public referral hospitals in low-income communities, as well as the associated obstetric and neonatal risk factors and mortality outcomes. Improving care for high-risk women during labor and delivery has been shown to reduce the risk of perinatal events and the development of BA.